Oral Manifestations of Primary Sjogren’s Syndrome with an Interdisciplinary Management Approach – A Case Report - Sadaksharam Jayachandran; M Archana (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Sjogren’s syndrome (SS) is a chronic autoimmune disease with a prevalence of 1%, characterized by inflammation of the exocrine glands, especially the salivary and lacrimal glands, leading to the sicca syndrome and systemic manifestations. Oral manifestations are encountered with high frequency in chronic autoimmune diseases like SS and are often the first clinical signs or symptoms leading to the diagnosis of the systemic disease. Xerostomia, gingivitis, rampant dental caries, tongue depapillation, dry cracked lips, oral candidiasis, and salivary gland enlargement are the common oral manifestations of SS. These oral lesions should be systematically managed using a holistic approach to improve the quality of life of the patient. In this paper, we are presenting a case of primary SS in a young female patient managed using an interdisciplinary approach with a focus on the management of oral conditions. In this case, we used transcutaneous electrical nerve stimulation (TENS) therapy to stimulate the salivary glands. At the end of the 14th appointment of TENS, the salivary flow rate was increased to 0.3 mL/min from 0.1 mL/min with symptomatic relief. In this case, we found an increase in the salivary flow rate at the end of TENS therapy, suggesting that it may be useful as an effective supportive treatment modality in SS patients. It is a noninvasive and painless mode of therapy. Early diagnosis and intervention of autoimmune diseases leads to decreased morbidity and improved quality of life of the patient. The reader should understand that an interdisciplinary approach is to be followed for the overall management of the disease with the involvement of primary care doctors, rheumatologists, ophthalmologists, and experts in oral medicine.